Advanced graphene oxide synthesis for arsenic removal from groundwater in Mexico and Colombia - J.P. Rodríguez-Caicedo; D.R. Joya-Cárdenas; A. Gallegos-Muñoz; M.R. Abraham-Juárez; M. Zapata-Torres; C.E. Damián-Ascencio; A. Saldaña-Robles (Results in Engineering)
This study presents the optimization of graphene oxide (GO) synthesis for arsenic (As) removal from contaminated groundwater in Mexico and Colombia, using the modified Hummers method. By applying response surface methodology (RSM), the concentrations of NaNO₃ and KMnO₄ were adjusted to maximize the density of oxygenated functional groups, significantly enhancing the adsorption capacity for As(V). Characterization results revealed a reduction in macroporosity and an increase in mesoporosity and microporosity, contributing to the superior adsorption performance. The optimized GO achieved an adsorption capacity of 99.13 mg g⁻¹ at 308 K under competitive conditions with other ions such as F⁻, CrO₄²⁻, Cl⁻, CO₃²⁻, and SO₄²⁻. Additionally, the synthesis process reduced toxic by-products, demonstrating sustainability for industrial-scale applications. These findings represent a significant advancement in the development of efficient and sustainable materials for groundwater remediation.